Concepts for Teaching Speaking in the English Language Classroom - Saud, Padama Bhandari (KVM Research Journal, 2025)
One part of teaching English that is frequently overlooked is teaching speaking in a systematic and precise manner. Even while teachers might be offering a variety of speaking exercises in the classroom, these exercises might really be more like "doing speaking" than "teaching speaking."In this piece, I contend that knowing the "combinatorial" nature of speaking—that is, the linguistic and discursive aspects of speech, the fundamental speaking abilities that allow speakers to comprehend and generate speech, and the communication techniques for facilitating and sustaining spoken interactions—is essential to being a skilled speaking instructor. In order to construct assignments and activities that specifically address these speaking characteristics and scaffold student learning, teachers might utilize the "teaching-speaking cycle" (Goh and Burns, 2012) that is presented in the article’s conclusion.